2014
DOI: 10.17557/tjfc.45522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Application on Biomass Accumulation, Remobilization, and Soil Water Contents in a Rainfed Wheat Field

Abstract: Our results suggested that N fertilization at 150 kg N ha 1 was optimal for grain production via promoting above-ground biomass and soil water consumption in deep soil layers. These results should help provide guidance for N fertilization management for optimal and sustainable wheat production in the said region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Haile et al [46] reported that different rates of N fertilization significantly increased wheat grain yield, and its maximum was achieved by application of 120 kg N ha −1 (however, optimal yield was not achieved as the response apparently did not plateau out). Litke et al [47] observed a significant wheat grain yield increase up to the rate of 180 kg N ha −1 , and Duan et al [48] up to the rate of 150 kg N ha −1 . According to Ali et al [49], increasing N doses increase plant height as they stimulate the vegetative development, and thus grain yield is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Haile et al [46] reported that different rates of N fertilization significantly increased wheat grain yield, and its maximum was achieved by application of 120 kg N ha −1 (however, optimal yield was not achieved as the response apparently did not plateau out). Litke et al [47] observed a significant wheat grain yield increase up to the rate of 180 kg N ha −1 , and Duan et al [48] up to the rate of 150 kg N ha −1 . According to Ali et al [49], increasing N doses increase plant height as they stimulate the vegetative development, and thus grain yield is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Silva et al [7] did not prove that different N rates affect wheat yield. Duan et al [29] proved that the grain yield of winter wheat under 150 kg N ha -1 increased from 51.4 to 66.6% compared with controls. In the present experiment, intensive mineral fertilization, including the increase in the fertilizer rate by 100%, resulted in an increase in grain yield on average by 0.31 t ha -1 , i.e., by 6.4%.…”
Section: Spring Wheat Productivitymentioning
confidence: 99%
“…Its lack may be an abiotic stress that reduces yield (Zhang et al, 2007). Higher nitrogen application rates increased the accumulation of dry matter (Duan et al, 2014). Aires et al (2006) stated that nitrogen is one of the most important factors affecting plant growth as well as the biosynthesis of secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%